Solvent concentration effect on total flavonoid and total phenolic contents of Averrhoa bilimbi leaf extract - Muhammad Ryan Radix Rahardhian; Bayu Tri Murti; Dyah Wigati; Ririn Suharsanti; Chintiana Nindya Putri (Pharmaciana, 2019)
Averrhoa bilimbi is one of the Indonesian indigenous plants containing phenolic and flavonoids which exhibit several ethnopharmacological effects i.e. antidiabetic, anti-microbial, anti-inflammatory, cytotoxic, anti-oxidant, antifertility, and antibacterial activities. However, the optimum solvent for extracting these compounds using percolation have not been reported, yet. This research was aimed to evaluate the various concentrations of ethanol solvents towards total phenolic (TPC) and total flavonoid content (TFC). Extraction was carried out using percolation technique with ethanol solvent ratio of 50%, 70%, and 96%. The phytochemical screening, thin layer chromatography, total flavonoids, and total phenolic levels were obtained from the concentrated extract. The TPC and TFC were determined using visible spectrophotometry method. Phytochemical screening study indicated that ethanolic extract contains classes of flavonoids, phenolic, alkaloid, saponins, and steroids. The TFC of ethanolic extract with 50%, 70%, and 96% solvent concentrations were investigated at 62.74, 64.81 and 59.1 mg RTE / g extract, respectively while the TPC were recorded as follows: 103.79; 119.47; 110.10 mg GAE / g extract. Hence, 70% ethanol were higher among others, and therefore remains as optimum solvent for the extraction of A. bilimbi leaves.Â